2013
DOI: 10.1016/j.exer.2012.11.012
|View full text |Cite
|
Sign up to set email alerts
|

M2/M1 ratio of tumor associated macrophages and PPAR-gamma expression in uveal melanomas with class 1 and class 2 molecular profiles

Abstract: Macrophages have been found to be negative predictors of outcome in patients with uveal melanoma. In particular, recent studies point towards a disease-progressing role of proangiogenic M2 macrophages in melanomas with monosomy 3. Although most studies implicate a protective effect of PPAR-gamma activation in tumors, PPAR-gamma has also been shown to promote the polarization of M1 macrophages towards the M2 phenotype. The purpose of this investigation was first, to characterize the phenotype of tumor infiltrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 31 publications
(57 reference statements)
2
41
0
Order By: Relevance
“…We show for the first time, that intratumoral TLR7/8 agonist shifts the intratumoral M1/M2 macrophage ratio, and importantly, that these macrophages and their chemokine CCL2 are important for tumor control. M2 to M1 polarization of TAMs by 3M-052 holds promise for clinical application, since high M2/M1 TAM ratios are considered as a poor prognostic factor in multiple cancers including cutaneous and uveal melanoma and lung cancer (15, 3740). In contrast, O'Sullivan et.…”
Section: Discussionmentioning
confidence: 99%
“…We show for the first time, that intratumoral TLR7/8 agonist shifts the intratumoral M1/M2 macrophage ratio, and importantly, that these macrophages and their chemokine CCL2 are important for tumor control. M2 to M1 polarization of TAMs by 3M-052 holds promise for clinical application, since high M2/M1 TAM ratios are considered as a poor prognostic factor in multiple cancers including cutaneous and uveal melanoma and lung cancer (15, 3740). In contrast, O'Sullivan et.…”
Section: Discussionmentioning
confidence: 99%
“…Urokinase‐type plasminogen activator receptor and matrix metallopeptidase‐9, which are expressed by both tumour cells and TAMs, enhance tumour invasion . Recent studies show a disease‐progressing role of proangiogenic M2 macrophages in uveal MMs with monosomy 3, and association of TAMs with tumour aggressiveness and poor prognosis in sinonasal MM . Overall, the role of TAMs in cutaneous MM still needs further clarification.…”
Section: Cells Of the Skin Immune Systemmentioning
confidence: 99%
“…Generally, redirecting hallmarks of cancer by communicative reprogramming leads to long‐term tumour control in histologically quite different neoplasias1, 2: A recently published randomized phase II trial on metastatic melanoma revealed significant impact of pioglitazone, a peroxisome proliferator‐activated receptor γ (PPAR γ )3, 4 agonist, on inflammation control, progression‐free survival and overall survival when added to immune‐modulatory and angiostatic acting metronomic low‐dose chemotherapy 5, 6, 7…”
Section: Figurementioning
confidence: 99%